FAMILY PERCEPTION OF LIFE-SUSTAINING TREATMENT WITHDRAWAL IN PATIENT WITH SEVERE BRAIN INJURY: A QUALITATIVE STUDY IN BANDUNG-INDONESIA - Hidayat, Gezira Azka Aulia; Huspa, Fitri Agustina; Syukriani, Yoni Fuadah (Jurnal Forensik dan Medikolegal Indonesia, 2023)
Background: The decision-making process for withdrawing life-sustaining treatment (LST) in patients with severe brain injury can potentially become a problem between doctor and family because of different opinions. Objective: Explore the family consideration in withdrawing LST in patients with severe brain injury. Methods: This qualitative descriptive study with phenomenological approach conducted using semi-structured in-depth interview. Subjects were family members of coma patients due to severe brain injury and were admitted to the Intensive Care Unit in Hasan Sadikin General Hospital during January 2019 - December 2020. Results: The results of the five-participant interview showed that the considerations for withdrawing LST include: (1) the patient's condition, (2) family psychology, (3) resources, and (4) family beliefs. Conclusion: Doctors need to understand the family's considerations in terminating LST to bridge the inner conflicts that occur in the patient's family.